2018
DOI: 10.1186/s40781-018-0172-x
|View full text |Cite
|
Sign up to set email alerts
|

Maximum number of total born piglets in a parity and individual ranges in litter size expressed as specific characteristics of sows

Abstract: Background: The objective of this study was to underline that litter size as a key trait of sows needs new parameters to be evaluated and to target an individual optimum. Large individual variation in litter size affects both production and piglet's survival and health negatively. Therefore, two new traits were suggested and analyzed. Two data sets on 5509 purebred German Landrace sows and 3926 Large White and crossing sows including at least two parental generations and at least five parities were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…In groups S and M, a significant increase of litter size was noted until the 4th parity and then showed alternate relevant peaks and nadirs. These results are consistent with research conducted by Freyer [26], where the greatest litter sizes were also reached by sows in their fourth parity. On the other hand, some researchers showed that the number of piglets born per litter increases with sows’ parity, reaching a peak between 2 to 5 parities [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…In groups S and M, a significant increase of litter size was noted until the 4th parity and then showed alternate relevant peaks and nadirs. These results are consistent with research conducted by Freyer [26], where the greatest litter sizes were also reached by sows in their fourth parity. On the other hand, some researchers showed that the number of piglets born per litter increases with sows’ parity, reaching a peak between 2 to 5 parities [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Despite long‐term selection and high genetic gains achieved already for litter size in pigs, there are no signs of decline in genetic variation and heritability of this trait (Nielsen, Su, Lund, & Madsen, ; Putz, Tiezzi, Maltecca, Gray, & Knauer, ; Trenhaile, Petersen, Kachman, Johnson, & Ciobanu, ; Varona, Legarra, Herring, & Vitezica, ; Zhang et al, ). Still large variation in litter size between sows exists (Freyer, ; Sell‐Kubiak, Wang, Knol, & Mulder, ). In addition, the sizes of the consecutive litters of the same sow also fluctuate, that is, there is a within‐sow variation (Hoving, Soede, Graat, Feitsma, & Kemp, ; Hughes, Wiseman, Varley, Kemp, & Varley, ; Koketsu & Dial, ).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the TNB at a certain optimum rather than continuously increasing, it may be a good approach in terms of litter size variability control. Freyer (2018) reported that sows with litters from 14 to 16 piglets tend to have the smallest variability across subsequent parities. Also, a similar optimum for TNB is expected from the biological point of view, since the number of piglets should not exceed the number of teats (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, both traits must have EVs from a strictly defined and small range to provide a simultaneous change of both traits in the desired directions. Also, Freyer (2018) reported a positive genetic correlation between individual maximum numbers of piglets born and variability of litter size treated as a difference between the maximum and minimum observed litter sizes. However, the opposite sign of the correlation between litter size and its variability was reported in pigs by Felleki et al (2012) and in rabbits by Argente, Calle, Garcia, and Blasco (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation